Walk among us : three novellas of the world of darkness - Gornichec, Genevieve; Khaw, Cassandra; Starling, Caitlin (Vampire: the masquerade, 2020)
In Genevieve Gornichec's A SHEEP AMONG WOLVES, depression and radicalization go hand-in-hand as a young woman finds companionship in the darkness. In Cassandra Khaw's FINE PRINT, an arrogant tech bro learns the importance of reading the fine print in the contract for immortality. And in Caitlin Starling's THE LAND OF MILK AND HONEY, ideals and ethics bump heads with appetite on a blood farm. Three very different stories from three amazing, distinct voices, but all with one thing in common: the hunger never stops, and for someone to experience power, many others are going to have to feel pain